A Novel Method of Determining the Functional Effects of a Minor Genetic Modification of a Protein - Nagwekar, Janhavi; Duggal, Divya; Midde, Krishna; Rich, Ryan; Liang, Jingsheng; Kazmierczak, Katarzyna; Huang, Wenrui; Fudala, Rafal; Gryczynski, Ignacy; Gryczynski, Zygmunt; Szczesna-Cordary, Danuta; Borejdo, Julian (Frontiers in Cardiovascular Medicine, 2015)
Contraction of muscles results from the ATP-coupled cyclic interactions of the myosin cross-bridges with actin filaments. Macroscopic parameters of contraction, such as maximum tension, speed of shortening or ATPase activity, are unlikely to reveal differences between the Wild Type and mutated proteins when the level of transgenic protein expression is low. This is because macroscopic measurements are made on whole organs containing trillions of actin and myosin molecules. An average of the information collected from such a large assembly is bound to conceal any differences imposed by a small fraction of mutated molecules. To circumvent the averaging problem, the measurements were done on isolated ventricular myofibril in which thin filaments were sparsely labeled with a fluorescent dye. We isolated a single myofibril from a ventricle, oriented it vertically (to be able measure the orientation), and labeled 1 in 100,000 actin monomers with a fluorescent dye. We observed the fluorescence from a small confocal volume containing ~3 actin molecules. During the contraction of a ventricle actin constantly changes orientation (i.e. the transition moment of rigidly attached fluorophore fluctuates in time) because it is repetitively being “kicked” by myosin cross-bridges. An autocorrelation functions of these fluctuations are remarkably sensitive to the mutation of myosin. We examined the effects of Alanine to Threonine (A13T) mutation in the myosin regulatory light chain shown by population studies to cause hypertrophic cardiomyopathy. This is an appropriate example, because mutation is expressed at only 10% in the ventricles of transgenic mice. Autocorrelation functions were either “Standard” (decaying monotonically in time) or “Non-standard” (decaying irregularly). The sparse labeling of actin also allowed the measurement of the spatial distribution of actin molecules. Such distribution reflects the interaction of actin with myosin cross-bridges and is also remarkably sensitive to myosin mutation. The result showed that the A13T mutation caused 9% autocorrelation functions and 9% of spatial distributions of actin to be non-standard, while the remaining 91% were standard, suggesting that the nonstandard performances were executed by the mutated myosin heads and that the standard performances were executed by non-mutated myosin heads. We conclude that the method explored in this study